2018
DOI: 10.1177/0020852317753528
|View full text |Cite
|
Sign up to set email alerts
|

Corruption in migration management: a network perspective

Abstract: This article explores the relation between networks as an emerging mode of public governance and corruption. Adopting the theoretical lens of actor-network theory, the article investigates an Italian episode of corruption related to the awarding of government contracts for the management of Mineo’s CARA, Europe's largest reception centre for migrants. The analysis shows that a governance network may turn corruption itself into a network where abuse of power can proliferate thanks to the opacity resulting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 44 publications
(63 reference statements)
0
17
0
1
Order By: Relevance
“…Opacity is a key condition for corruption schemes to remain discreet (Ionita 2005; Berkovich 2016; Pianezzi and Grossi 2018; Sancino et al 2018). We defined opacity drawing from the literature and our findings, which allows us to see it as a lack of transparency in procedures (Bauhr et al 2019), reflected, also, in ambiguity and uncertainty (Chan 2001).…”
Section: Towards a Theory Of Corruption Consolidationmentioning
confidence: 99%
See 2 more Smart Citations
“…Opacity is a key condition for corruption schemes to remain discreet (Ionita 2005; Berkovich 2016; Pianezzi and Grossi 2018; Sancino et al 2018). We defined opacity drawing from the literature and our findings, which allows us to see it as a lack of transparency in procedures (Bauhr et al 2019), reflected, also, in ambiguity and uncertainty (Chan 2001).…”
Section: Towards a Theory Of Corruption Consolidationmentioning
confidence: 99%
“…Alternatively, corruption is explained as part of a social institution or along a structural dimension (De Graaf 2007;De Graaf and Huberts 2008;Graycar and Villa 2011;Jancsics and Jávor 2012;Beeri and Navot 2013;Pianezzi and Grossi 2018;Persson et al 2019). These approaches include the focus on networks rather than on dyadic interactions (De Graaf and Huberts 2008;Jancsics and Jávor 2012;Pianezzi and Grossi 2018;Yu et al 2020).…”
Section: Two Approaches To Corruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of them have been closed by the government following criticisms about human rights violations and corruption scandals. A case in point was the Mineo's CARA in Sicily, Europe's largest reception centre for migrants hosting over 2,000 irregular immigrants and closed in 2019 following a corruption scandal (Pianezzi & Grossi, 2018). Despite they are called "governmental centres", the management of these big centres is usually outsourced to non-governmental organizations through tender and with accounting mechanisms analogous to those that regulate the so-called CAS system described below.…”
Section: The Parallel System Of Cass and Governmental Centres: Neoliberalising The Statementioning
confidence: 99%
“…Corruption usually moves from individuals who act in their own interests at the expense of an organization (as in the case of embezzlement), but it sometimes expands to involve a whole array of actors. Many studies have shown that public employees are often among the leaders of corruption networks (Beeri et al, 2013;Neu et al, 2013;Sargiacomo et al, 2015;Vaidya, 2019;Pianezzi and Grossi, 2020). Governments frequently announce anticorruption schemes, but they seem to have little effect.…”
Section: Accounting Can Support "Sustainable" Networkmentioning
confidence: 99%